A Workflow-Oriented System Architecture for the Management of Container Transportation - Bassil, Sarita; Keller, Rudolf K.; Kropf, Peter (My University, 2004)
In this paper, we introduce a workflow-oriented system architecture for the processing of client requests (CRs) for container transportation. In the context of multi-transfer container transportation, the processing of CRs can be achieved by specific sequences of interdependent activities. These sequences need to be just-in-time created. They also need to be adapted to deal with unexpected events that may occur. Workflow technology is used to model and to manage the processing of CRs. The creation and the adaptation of activity sequences require first, an optimized scheduling of a limited number of resources (by also respecting CRs constraints); and second, a number of special workflow concepts and functionality to correctly manage activity sequences. Optimization models are involved to take care of the resource management and of the activity scheduling. Enhancements of workflow concepts and functionality for workflow management systems are investigated to deal with an activity sequence creation and adaptation. Finally, the proposed architecture includes a rule processing part to reduce the time-consuming manual interaction with the system.
Keywords: system architecture; workflow management system; process planning; flexible workflow; transportation application